1980
DOI: 10.1007/bf00405956
|View full text |Cite
|
Sign up to set email alerts
|

Does acrolein contribute to the cytotoxicity of cyclophosphamide?

Abstract: To determine whether the release of acrolein from oxazaphosphorinane-cytostatics contributes to their cytotoxic action, the effect of 4-hydroperoxycyclophosphamide, 4-hydroperoxy-semi-cyclophosphamide, 4-hydroperoxy-dechloro-cyclophosphamide, and acrolein on murine L 1210 leukemia cells in vitro was compared by measuring the median survival time (MST) after transplantation of the tumor cells in DBA2/Han mice. We found that only 4-hydroperoxycyclophosphamide, which is able to release both acrolein and the alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…The possibility of such a sensitising action has been suggested by Alarcon and Meienhofer (1971) for acrolein, but no supporting evidence has been presented. In agreement with previous findings (Brock, 1976;Wrabetz et al, 1980), we have also demonstrated the relative lack of toxicity of acrolein ( Figure 4a). Thus, deschloro-4-hydroperoxycyclophosphamide, which has its bis-(P-chloroethyl)amine group replaced by diethylamine, produced acrolein (Alarcon & Meienhofer, 1971) and depleted cellular GSH as efficiently as 4-OOH-CP (Figure 4b), but was non-cytotoxic because it cannot give rise to PM (Figure 4a).…”
Section: Effects Of Cellular Gsh Content On the Alkylating Capacity Osupporting
confidence: 93%
“…The possibility of such a sensitising action has been suggested by Alarcon and Meienhofer (1971) for acrolein, but no supporting evidence has been presented. In agreement with previous findings (Brock, 1976;Wrabetz et al, 1980), we have also demonstrated the relative lack of toxicity of acrolein ( Figure 4a). Thus, deschloro-4-hydroperoxycyclophosphamide, which has its bis-(P-chloroethyl)amine group replaced by diethylamine, produced acrolein (Alarcon & Meienhofer, 1971) and depleted cellular GSH as efficiently as 4-OOH-CP (Figure 4b), but was non-cytotoxic because it cannot give rise to PM (Figure 4a).…”
Section: Effects Of Cellular Gsh Content On the Alkylating Capacity Osupporting
confidence: 93%
“…Because AC is a well known cytotoxic agent [17-191, several investigators have attempted to elucidate what role, if any, AC plays in the antitumor properties of CP. Using an analog of CP (4-hydroperoxydechlorocyclophosphamide), which releases AC but not an alkylating species (PM), Wrabetz et a1 [18] were able to show that AC generated by the metabolism of CP did not contribute to the cytotoxic (antineoplastic) activity of CP. Moreover, they pointed out that, although AC itself was cytotoxic, the mechanism of cytotoxicity of "extracellular" AC differed from that produced by CP.…”
Section: Role Of Metabolites In Cp Antitumor Effectsmentioning
confidence: 99%
“…In order to corroborate these findings, Mirkes et al [73] took another approach. They exposed embryos in vitro to dechlorocyclophosphamide (D-CP), which is metabolized in a manner similar to CP [74,75] and forms AC but not PM. Using this derivative of CP it was possible to expose embryos to AC without the simultaneous exposure to PM.…”
Section: Cp Teratogenesis In Vltro Role Of Cp Metabolitesmentioning
confidence: 99%
“…[14] With the new approach, locally produced acrolein should have a much reduced side effect on other organs. The pharmacological properties of prodrug 13 are currently under investigation.…”
Section: Resultsmentioning
confidence: 99%